Análisis de la aplicación de la ley orgánica de solidaridad y de corresponsabilidad ciudadana para la reconstrucción y reactivación de las zonas afectadas por el terremoto de 16 de abril de 2016 y su incidencia en la compañía de transporte pesados de Cotopaxi COTRAPECSA S.A. - Changoluisa Quishpe, Tania Maricela (2018)
The present research has the objective to determine the incidence of application of the Solidarity Organic Law and citizen co-responsibility for the reconstruction and reactivation of the zones affected by the earthquake of April 16, 2016 and its incidence on the heavy Transport Company of Cotopaxi COTRAPECSA S.A, by the contribution paid later its application. A study and review of the law before mentioned and the four components of the same will be made in order to determine the variation generated on the tax process and profit on the financial period of application of this legal body. For the study implementation an investigative focus of quantitative character was used, which would facilitate the collection of information, with techniques and research instruments like the interview to the Accountant, and the surveys focuses on the Company's shareholders, finally the direct observation of the Financial Statements, allowed to collect information in order to achieve the proposed objectives. The main conclusions of this research are, the Company was benefited after the disaster, evidencing a notable incidence in its profitability. During this period an increase in the income from transportation services was seen, this statement matches with the Accountant’s answer, who indicated that the reconstruction process of the affected zones generated greater demand for the service, increasing the profit of the company. Key words: incidence, application, profitability, increase.